Antioxidant, antimicrobial activities and comparative analysis of the composition of essential oils of leaf, stem, flower and aerial part of Nepeta hindostana. (4th March 2019) - Siddique, Amreen A.; Gupta, Priyanka; Singh, Shilpi; Gupta, Madhuri; Misra, Laxminaraian; Darokar, Mahendra P.; Luqman, Suaib; Yadav, Anju; Bhakuni, Rajendra S.
Abstract: Nepeta hindostana (B.Heyne ex Roth) Haines is belonging to lamiaceae family and used as a component of herbal ayurvedic formulation Abana which is useful for the treatment of Hyperlipidemia, Dyslipidemia and Hypercholesterolemia. In the present study, the essential oil from aerial parts (flower, leaves, stem and whole aerial) was collected and the major constituents of essential oils were characterized by GC-FID and GC/MS and further evaluated for their antioxidant and antimicrobial efficacy. The major components of the essential oil were sesquiterpene hydrocarbons (77.2, 80.5, 62.5, 77.8%), oxygenated sesquiterpenes (10.5, 9.2, 20.6, 9.2%) and oxygenated monoterpenes (5.3, 4.2, 2.5, 3.6%) in leaves, stem, flowers and aerial part, respectively. The major compounds in essential oils were identified as β-sesquiphellandrene, cadina-1, 4-diene, α-cadinene, ( E )-caryophyllene, α-humulene and β-bisabolene. At 100 μg/mL concentration, leaves essential oil showed strong 2, 2-diphenyl-1-picryl-hydrazyl-hydrate free radical scavenging activity with the IC50 2.8 μg/mL and 34.0% by β-carotene bleaching assay. Furthermore, the antibacterial activity was tested against four Gram-negative and five Gram-positive pathogenic strains. The essential oil from flower showed potent activity (37.5 μg/ml) against S. aureus, S. mutans but was less active against Gram-negative bacterial strains. In anti-MRSA activity, leaves and flowers exhibited strong activity against S. aureus (SA-2071) and S. aureus (SA-4627) with lowest IC50 value of 50–100 μg/mL. Overall, N. hinodostana (L.) essential oil represented a potential reservoir of molecules having potent antioxidant and antimicrobial potential.